Hubungan Tingkat Pengetahuan Dan Pola Asuh Orangtua Dengan Persepsi Orangtua Terhadap Kecerdasan Emosi Pada Anak Usia Pra Sekolah (3-6 Tahun) Di Taman Kanak-Kanak Aisyiyah 1 Kota Bukittingi Tahun 2024 - Nora, Rista Nora; Anisa Sri Utami (Jurnal Amanah Kesehatan, 2025)
ABSTRACT In raising and educating children, it is influenced by several factors including past experiences that are closely related to parenting patterns or parental knowledge, values ​​adopted by parents, personality types of parents, parents' marital life and the reasons for parents to have children. Aisyiyah Kindergarten 1 Bukittinggi City is a Kindergarten with the largest number of students. This study aims to determine the relationship between the level of knowledge and parenting patterns of parents with emotional intelligence in preschool children (3-6 years) at Aisyiyah Kindergarten 1 Bukittinggi City in 2024. This type of research is descriptive analytical with a cross-sectional study design conducted at Aisyiyah Kindergarten 1 Bukittinggi City, from October to December 2024. The study population was all parents who had children at Aisyiyah Kindergarten 1 Bukittinggi City, totaling 170 people. sampling by accidental sampling. the sample according to the researcher's criteria was 43 respondents. Data collection was carried out by questionnaires, interviews and observations. The results of the univariate analysis showed that 57.5% of mothers' knowledge was low, 58.8% of mothers' parenting patterns were lacking and 45.0% of mothers' children had low emotional intelligence. The results of the bivariate analysis showed a significant relationship between the level of knowledge and parenting patterns of parents with the emotional intelligence of preschool children at Aisyiyah Kindergarten 1 Bukittinggi City in 2024. The low emotional intelligence in children is recommended through the leadership of Aisyiyah Kindergarten 1 Bukittinggi City to provide information to parents about the importance of paying attention to children's emotional intelligence.